Pengaruh Belanja Online Terhadap Perilaku Konsumtif Dan Gaya Hidup Pada Mahasiswa Pendidikan Ekonomi Universitas Hamzanwadi Angkatan Tahun 2020 - Hafiz, Nur Fitriani; Riswanto, Agus (Alpatih Harapan Semesta, 2024)
This research aims to determine the direction of the impact of online shopping on consumer behavior and lifestyle among economic education students at Hamzanwadi University. The research sample consisted of 52 students from the class of 2020 from a total population of 110 students, using quantitative methods. And simple random sampling technique. Data was collected through questionnaires distributed using Google Form, and analyzed using validity, reliability, normality, linearity, simple linear regression and t tests. The results of the analysis show that online shopping has a positive and significant influence on student consumption behavior and lifestyle. For variable X against Y1, the value of tcount > ttable (5,716 > 2,010), and for variable Thus, it can be concluded that online shopping has a positive and significant impact on consumption behavior and lifestyle of economics education students at Hamzanwadi University.